Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1590/s0034-71672005000400008
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados com a incontinência urinária na mulher

Abstract: Artigo extraído da dissertação de mestrado apresentada ao Curso de Pós-Graduação em Enfermagem da Faculdade de Ciências Médicas da UNICAMP RESUMOTrata-se de um estudo para avaliar a prevalência da incontinência urinária (IU) e fatores associados entre mulheres profissionais de enfermagem de um hospital-escola. INTRODUÇÃONa população feminina, a experiência com episódios de perda urinária é uma condição que ocorre não somente entre mulheres idosas, mas também entre mulheres jovens e na meia-idade. Os problemas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
2
17

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 23 publications
(33 reference statements)
4
10
2
17
Order By: Relevance
“…Despite the fact that no statistically significant differences were found, the present study showed a slight predominance of UI among the primiparae, which disagrees with other studies performed in Brazil (14)(15)21) and in Europe (13 ) , which found that UI was more common among multiparae women. A study performed in Norway (3 ) , with 4,662 primiparae and 3,549 multiparae, found that parity is a strong risk factor for UI during pregnancy and that the UI prevalence is greater among women who have experienced childbirth.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that no statistically significant differences were found, the present study showed a slight predominance of UI among the primiparae, which disagrees with other studies performed in Brazil (14)(15)21) and in Europe (13 ) , which found that UI was more common among multiparae women. A study performed in Norway (3 ) , with 4,662 primiparae and 3,549 multiparae, found that parity is a strong risk factor for UI during pregnancy and that the UI prevalence is greater among women who have experienced childbirth.…”
Section: Discussioncontrasting
confidence: 99%
“…In literature, studies state that urinary incontinence affect up to 74% of the formerly continent pregnant women (10)(11)(12) . Considering a population of age between 17 and 45 years, studies show UI prevalence in the postpartum between 20% and 27.5% (10,(12)(13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] In Brazil, data on prevalence of UI in middle aged women usually relate to stress UI (SUI), reaching 8 to 48%. [8][9][10][11][12][13][14] Moreover, there is a disturbing economic impact on the health system, seen, for example, in the costs in Brazil in 2014; the total spent on women between 30 and 59 years totaled more than BRL 2 billion, and of these, BRL 183 million were directed to genitourinary diseases. Surgeries for female genital prolapse, one of the causes of UI included in the ICD-10, generated in 2014 a cost of BRL 15.8 million (8.7%).…”
Section: Introductionmentioning
confidence: 99%
“…In general, UI affects 19% of women between 19 and 44 years old, 25% of women between 45 and 64 years old and 30% of women above 65 years old (11). SUI is the most common type of UI, affecting younger women between 25 and 49 years old (10,12,13,14,15) while UI and MUI are more prevalent in women above 60 years old.…”
Section: Introductionmentioning
confidence: 99%